The prevalence of human papillomavirus genotypes in penile cancers from northern Thailand - Masachika Senba (2018)
The highest frequency of penile cancer occurs in Asia, Africa, and Latin America, and there have been a few reports concerning the association of penile cancer with human papillomavirus (HPV) infection in these areas. The objective of this study was to determine the relation between penile cancer and the prevalence of HPV genotypes in northern Thailand. Eighty-eight specimens of penile tissue (65 malignant, 1 premalignant, and 22 benign cases) were examined to determine the association of HPV infection. An in situ hybridization (ISH) method was used to detect and localize HPV-DNA. Sensitive HPV polymerase chain reaction (PCR) procedure was used for detection of HPV-DN A, and DNA sequencing was used to identify the HPV genotype. HPV-DNA was detected in 53.8% and 81.5% of cases of penile cancer, using ISH and PCR, respectively. The high-risk HPV-16, most commonly associated with penile cancer in previous reports, was found in only one case in this study. Themost prevalent genotype was the high-risk HPV-18, found in 55.4% of the cases (32.3% single and 23.1% multiple infection) followed by the low-risk HPV-6, found in 43.1% of the cases (24.6% single and 18.5% multiple infection). In this study, penile cancer was found to be highly correlated with HPV-DNA. Specifically, infection with both the low-risk HPV-6 and the high-risk HPV-18 is the characteristic prevalence of HPV genotypes in penile cancer in this area. © 2006 Wiley-Liss, Inc.